A pilot study of intralesional methotrexate injections versus triamcinolone acetonide in patients affected by nail matrix psoriasis. (1st June 2022) - Starace, Michela; Alessandrini, Aurora; Iorizzo, Matilde; D'Altobrando, Ambra; Ferrari, Tiziano; Bruni, Francesca; Piraccini, Bianca Maria
Summary: Nail disorders in general are difficult to treat and often frustrating, and this is also the case with nail psoriasis, especially when it is limited to the nails, and not affecting joints. The quality of life of patients with nail psoriasis is negatively affected, owing to the chronic course of the disease and frequent relapses. The purpose of this study was to compare treatment response and maintenance of response during follow‐up of 12 patients with nail matrix psoriasis limited to a few nails, who were treated with intralesional injections of either methotrexate (MTX) 25 mg/mL or triamcinolone acetonide 10 mg/mL. Patients were treated every 6 weeks for 24 weeks and followed up for 6 months. Photographic documentation and assessment by Nail Psoriasis Severity Index were performed during each treatment session and at each follow‐up visit. At the end of the four treatment sessions, all patients had improvement of their disease, which continued during follow‐up, especially for the MTX‐treated group. Abstract : The purpose of this study was to compare the response to treatment and follow‐up of 12 patients with nail matrix psoriasis, limited to few nails, treated with intralesional injections of methotrexate 25 mg/mL or triamcinolone acetonide 10 mg/mL.